SLOT-LINE FERROELECTRIC PHASE-SHIFTERS AND PHASE-ARRAY ANTENNA ON THEIR BASE - BUSLOV, O. YU; KEIS, V. N.; KOTELNIKOV, I. V.; GOLOVKOV, A. A.; SUGAK, M. I.; KOZYREV, A. B.; SENGUPTA, L. (Integrated ferroelectrics, 2006)
The experimental characteristics of the microwave phase-shifter based on the slot-line including ferroelectric film are presented. The tuning of the microwave signal phase at the slot-line output was provided due to the ferroelectric film dielectric permittivity variations under the DC control voltage application across the line slot. Phase shifter tested served as a basis for the 8-elemetns phase array antenna. The scanning sector of the steerable antenna was 60 deg and beam width was 13 deg.